PENGARUH STORE IMAGE, PRODUCT SIGNATURENESS, DAN QUALITY VARIATION TERHADAP REPURCHASE INTENTION PRODU PRIVATE LABEL MELALUI QUALITY PERCEPTION DI CARREFOUR SURABAYA - ., ANITA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This study aims to determine the effect of store image, product signatureness, and quality variation of repurchase intention through quality private label products in Carrefour Surabaya perception. This study uses analysis of Structural Equation Models, and methods used in this study is a survey directly to customers by distributing questionnaires Carrefour. The results of this study indicate that a significant influence Store Image Quality Perception of private label products, Product Signatureness have a significant effect on Quality Perception private label products, Quality Variation have a significant impact on Quality Perception private label products, Quality Perception have a significant effect on Repurchase Intention products private label, Image Store have a significant effect on Repurchase Intention private label products, Product Signatureness have a significant effect on Repurchase Intention private label products, and Quality Variation does not significantly influence to the Repurchase Intention private label products. Therefore, the Carrefour is expected to be able to improve the quality of merchandise in the future that will improve the image of the store (store image), thus making more and more customers interested in Carrefour's private label products.